Systematics, biogeography and conservation of Paragenidens grandoculis n. gen. and n. comb. (Siluriformes; Ariidae), a critically endangered species from southeastern Brazil - Marceniuk, Alexandre Pires [UNESP]; Da Silva Ingenito, Leonardo Ferreira; Thadeo Lima, Flavio Cesar; Rosetti Gasparini, Joao Luiz; Oliveira, Claudio [UNESP] (Magnolia Press, 2019)
Paragenidens, a new genus of ariid catfishes is proposed to accommodate Arius grandoculis, a species previously assigned to the genus Potamarius. Paragenidens grandoculis is an endemic ariid catfish categorized as Critically Endangered and probably Extinct from coastal lacustrine systems from Espirito Santo and Rio de Janeiro states, southeastern Brazil. After more than 50 years without records of the species, new recent fieldwork revealed that the species is extinct at lagoa Juparana, but still can be found at lagoa Nova in Linhares municipality, Espirito Santo state. Here, Paragenidens is described based on morphological and molecular evidence. In addition to its generic reassignment, the species is redescribed, and comments on its phylogenetic relationships, biogeography and conservation are presented.
Keywords: Threatened species; endemic; phylogenetic relationships; conservation; Atlantic rainforest; Paragenidens gen. n.